The Efektivitas Model CTL Dengan Media Burandut Untuk Mendukung Pemahaman Konsep Peserta Didik Kelas V - Meutia Revana Cahya Putri; Lovika Ardana Riswari; Eka Zuliana (Pusat Studi Bahasa dan Publikasi Ilmiah, 2026)
The low level of students’ mathematical conceptual understanding was evidenced by the Mid-Semester Assessment (STS) results for the 2025/2026 academic year. Students’ mathematics scores remained below the established Minimum Learning Achievement Criteria (KKTP) of 75, with the highest score reaching only 72. Moreover, 24 of 39 students had not achieved the KKTP. This condition indicates the need for meaningful and contextual learning to improve students’ mathematical conceptual understanding. This study aimed to determine the effectiveness of the Contextual Teaching and Learning (CTL) model assisted by Burandut media in supporting the mathematical conceptual understanding of fifth-grade students. The study employed a quantitative approach with a one-group pretest-posttest design involving 39 fifth-grade students at SD N 3 Demaan Kudus. Data were analyzed using the Shapiro-Wilk normality test, paired-sample t-test, and N-Gain test with SPSS version 25. The results showed that the data were normally distributed, with significance values of 0.258 for the pretest and 0.417 for the posttest, both exceeding 0.05. The paired-sample t-test obtained a significance value of 0.000 (<0.05), indicating a significant difference between the pretest and posttest scores. Furthermore, the N-Gain value was 0.66, categorized as moderate. Therefore, the CTL model assisted by BURANDUT media was moderately effective in supporting students’ mathematical conceptual understanding. The implementation positively contributed to students’ ability to understand, differentiate, represent, and relate angle concepts to real-life contexts. Thus, CTL assisted by Burandut media can be an alternative learning approach to support students’ mathematical conceptual understanding, particularly in angle material.